Internal Control In Accounting Information Systems - Sangkala, Masnawaty (Program Pascasarjana STIE Amkop Makassar, 2023)
When an organization implements accounting procedures, the accounting information system serves as a reference point. To prevent errors and omissions, whether intentional or unintentional, in the accounting procedures that produce financial reports, adequate guarantees must be provided. Bookkeeping data framework related to organization's business activities for example, classifying, recording and transmitting data as final product to achieve choice for internal and external parties. With the change of events innovative data bookkeeping frameworks have moved from manual to mechanical. The purpose of this article is to show how accounting information systems use internal controls. Companies that use information systems need computer-based accounting with integrated internal controls to help them reduce the risks associated with using computer- based accounting information systems for business processes. Keywords: Internal Control, Accounting Information Systems, Accounting.